Isolation and Identification of Saccharomyces boulardii as a Probiotic Yeast and Investigation of its In vitro and In vivo Beneficial Applications - Helmy, Eman A.; Abdel-Fadeel, Reda H.; El-Husseiny Helal, Eman; Yosri, Mohammed (Current Nutrition & Food Science, 2024)
Background: Yeasts are becoming increasingly popular as possible new resources to improve the nutritional value of food qualities like flavor, color, and vitamin content, as well as tools for preventing food spoiling due to their anti-microbial capabilities.Objective: This study aims to test the role of isolated Saccharomyces boulardii as a promising probiotic as well as Jerusalem artichoke as a prebiotic in a feeding animal model to test their possible functions in regulating lipid profile and bacterial count in the faeces of tested animals.Methods: For the isolation of yeast cultures on YM agar medium, five milk samples were randomly obtained from the Faculty of Agriculture at Al-Azhar University in Cairo, Egypt. S. boulardii was morphologically, physiologically, and molecularly identified and deposited in the gene bank; additionally, identification was confirmed using the BIOLOG system. For 30 days, researchers compared the roles of S. boulardii as a probiotic and Jerusalem artichoke as a prebiotic in controlling serum lipid profile and faeces microbial count in the tested animal groups.Results: The acid and bile tolerance tests illustrate the promising ability of S. boulardii. Additionally, S. boulardii could survive on simulated stomach and intestinal fluids. An in vivo feeding test showed that rats fed S. boulardii grew and gained weight faster. Furthermore, eating S. boulardii causes a marked increase in HDL levels and a marked drop in LDL, cholesterol, and triglycerides. Rats that consumed Jerusalem artichokes and a probiotic strain had significantly lower numbers of coliforms and Staphylococcus sp. in their stools.Conclusion: These results revealed the possible beneficial role of S. boulardii in overcoming hyperlipidemia, which should be applied on a large scale after verification of outcomes.
Keywords: faeces